PARADIGMA DAN AKTUALISASI INTERPRETASI DALAM PEMIKIRAN MUá¸¤AMMAD AL-GHAZÄ€LÄª - Iwanebel, Fejrian Yazdajird (Hunafa: Jurnal Studia Islamika, 2014)
Abstract. Muá¸¥ammad al-GhazÄlÄ« is one of the prominent thinkers of IkhwÄn al-Muslimin. He has been regarded by some scholars to possess progressive ideas and accomodative and contextual character. This paper, exemines the coherency of al-GhazÄlÄ«â€™s thought of interpretation and his paradigm manifested in his works on exegesis. In conclusion, the ideal interpretation paradigm offered by al-GhazÄlÄ« Â as knife analysis of the Koran textsÂ  is not fully applied. In fact, he intends to interpret the verses of the Koran textually. The question is where the inductive method of interpretation of the Koran which he thinks as the Qur'anic method. There is a discontinuityÂ  of thought which al-GhazÄlÄ« does not realize in reference to his paradigm for his interpretation.Kata Kunci: al-GhazÄlÄ«, interpretasi, paradigma, kontekstualisasi